Extensive onychomycosis in a patient with good syndrome - Ghadah AlHammad; Hatoun AlMaziad; Rayan AlKhodair (Wolters Kluwer Medknow Publications, 2019)
Thymoma with immunodeficiency was first reported by Dr. Robert Alan Good and was termed Good Syndrome. It is a rare acquired immunological disorder with <200 cases reported in the literature. Although described more than 60 years ago, the syndrome is still largely underrecognized by physicians who deal with the variable manifestations in the absence of diagnostic criteria. Here, we describe a patient with Good Syndrome diagnosed with extensive candidal onychomycosis. The patient had a history of excised thymoma and had myasthenia gravis. Further, laboratory investigations showed very low B-cells, CD4 helper T-cells and reduced CD4/CD8 consistent with the described abnormalities associated with Good Syndrome in the literature. Atypically severe variants of onychomycosis could indicate the presence of an immunodeficiency.